The effects of exercise on insulin, glucose, IGF‐axis and CRP in cancer survivors: Meta‐analysis and meta‐regression of randomised controlled trials. (11th December 2019) - Wang, Yafeng; Jin, Ben; Paxton, Raheem J.; Yang, Weili; Wang, Xirui; Jiao, Yurui; Yu, Chuanhua; Chen, Xiong
Abstract: Background: The purpose of this study was to investigate the relationship between physical activity and biological mediators of cancer recurrence and survival. Methods: We conducted a comprehensive literature search of PubMed, ScienceDirect and Web of Science for randomised controlled trials examining the association between physical activity and C‐reactive protein (CRP), glucose, insulin, insulin resistance and insulin growth factor‐one (IGF‐1) up to December 2017. Standardised mean difference (SMD) scores were calculated, and meta‐regression was performed. Results: The meta‐analysis indicated that survivors randomised to physical activity conditions experienced greater improvements in Insulin (SMD = −0.59; 95% CI, −1.05 to −0.14), CRP (SMD = −0.52; 95% CI, −0.87 to −0.17), insulin resistance (SMD = −0.20; 95% CI, −0.41 to −0.003) and glucose (SMD = −0.19; 95% CI, −0.35 to −0.02) than survivors randomised to control conditions. The meta‐regression showed that study duration was positively, albeit marginally related ( p  = .056) to change in CRP levels among survivors in the physical activity conditions. Furthermore, higher baseline insulin levels in the physical activity conditions were associated with improving insulin levels throughout the intervention ( p  = .007). Conclusions: Promoting physical activity throughout the survivorship continuum is an effective intervention strategy for improving levels of insulin, glucose control, insulin resistance and CRP among cancer survivors.